2017
DOI: 10.1111/plb.12535
|View full text |Cite
|
Sign up to set email alerts
|

Plant defence induced by PGPR against Spodoptera litura in tomato (Solanum lycopersicum L.)

Abstract: The S. litura infestation decreased dry weight of shoots and roots by 46% and 22%, and significant reduction was recorded in tomato fruit yield. The P. putida and Rothia sp. inoculations alleviated the adverse effects of insect infestation and resulted in 60% increase in plant biomass and 40% increase in yield over infested plants. Main conclusions including key points of discussion: PGPR: Defense appears to be mediated via increase in proline production, enhanced activities of antioxidant enzymes, stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 33 publications
3
50
0
Order By: Relevance
“…In our study, this family was the most abundant in the rhizosphere of both plants. With respect to the possible role in the plant tolerance to abiotic stress, several genus of this family have been described for their ability to control of plant pathogen [76], phosphate solubilization, phytohormone production, siderophores production [77,78].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, this family was the most abundant in the rhizosphere of both plants. With respect to the possible role in the plant tolerance to abiotic stress, several genus of this family have been described for their ability to control of plant pathogen [76], phosphate solubilization, phytohormone production, siderophores production [77,78].…”
Section: Discussionmentioning
confidence: 99%
“…Bano and Muqarab [48] investigated that the role of the PGPR, P. putida and Rothia sp., used to overcome the loss in tomato yield caused by Spodoptera litura (an insect). An infestation of tomato with S. litura reduced the dry weight of shoots and roots by 46% and 22%, respectively [48]. When surface-sterilized seeds of tomato were inoculated for 48 h with P. putida and Rothia sp., it was found that the effects of S. litura infestation were ameliorated and resulted in 60% and 40% increment in plant biomass and their yield, respectively, over infested plants [48].…”
Section: Mechanism Of Physiological Changes In the Host Plants And mentioning
confidence: 99%
“…Plant Growth Promoting Bacteria (PGPB) are beneficial strains naturally present in the rhizosphere of plants contributing to plant health. As it has been demonstrated certain strains trigger expression of some plant genes, defense related genes among others, enhancing plant defense metabolism; so when the pathogen tries to invade the plant, it is already prepared and not dramatically infected [14,15]. Therefore, PGPB appear as an alternative to chemical pesticides as well as tools to study plant metabolism.…”
Section: Introductionmentioning
confidence: 99%